Analisis Produktivitas Mesin Mixer Batching Ready Mix dengan Metode OMAX di Kalla Beton: Productivity Analysis of Ready Mix Batching Mixer Machine with OMAX Method at Kalla Beton - Arifin, Iskandar; Malik, Anhar (Elektriese: Jurnal Sains dan Teknologi Elektro, 2025)
Kalla Beton Unit Ready Mix Plant is a company that produces bulk concrete (ready mix). Until now, the company does not have a comprehensive understanding of the performance and level of production productivity, especially in the mixer batching plant machine. This mixer machine is the main component in production operations, so its efficiency and effectiveness greatly determine the company's output. This study aims to measure the productivity level of the mixer batching plant machine using the Objective Matrix (OMAX) Method. This method measures productivity separately in each production section, allowing for evaluation based on criteria by each section's functions and responsibilities. Productivity is a key factor in ensuring the success and sustainability of operations, so data-based analysis and evaluation are needed to improve company performance. In this study, the productivity of the mixer machine was measured based on three main criteria: raw material productivity, effective working hour productivity, and operational effectiveness of the mixer machine. The measurement results showed that the highest productivity value occurred in July, with an achievement of 5,822 tons/hour, while the lowest value occurred in April, with 2,374 tons/hour. A cause-and-effect diagram analysis was conducted to identify the causes of productivity fluctuations, which showed that the low season factor influenced the decline in productivity in the early to mid-year, where the number of orders was still relatively low. The findings of this study can be a basis for companies to design strategies for improving and increasing productivity, especially in optimizing the use of batching plant mixer machines to be more efficient and effective.